Liraglutide ameliorates diabetes-associated cognitive dysfunction via rescuing autophagic flux - Meng Zhang; Wenhui Yan; Ye Yu; Jie Cheng; Xinyao Yi; Tingli Guo; Na Liu; Jia Shang; Zhuanzhuan Wang; Hao Hu; Lina Chen (Elsevier, 2021)
The incidence of diabetes-associated cognitive dysfunction is increasing. However, few clinical interventions are available to prevent the disorder. Several researches have shown that liraglutide, as a glucagon-like peptide-1 analog, has protective effects on various neurodegenerative diseases, but its roles in diabetic cognitive dysfunction are rarely reported. This study aims to investigate the protective effects of liraglutide on diabetic cognitive dysfunction and its underlying mechanisms. In vivo, the effects of liraglutide treatment were investigated in a mouse model of type 2 diabetes mellitus (T2DM). In vitro, we investigated the effects of liraglutide on the high-glucose-induced rat primary neurons. The results showed that liraglutide reduced the escape latency and increased the time in effective area in the Morris water maze test, improved the damage of hippocampal and synaptic ultrastructure, and decreased the accumulation of amyloid β protein in hippocampus of T2DM mice. Furthermore, liraglutide increased the ratio of microtubule-associated protein light 1 chain Ⅱ/Ⅰ, the expression of Beclin1 protein and Lysosome-associated membrane protein 2 in vivo and vitro. Additionally, Bafilomycin A1 which can inhibit the fusion of autophagosome and lysosome partially abolished the effects of liraglutide. These findings indicate liraglutide ameliorates diabetes-associated cognitive dysfunction by rescuing autophagic flux.